THE FUTURE OF INTERRELIGIOUS DIALOGUE - John B. Chethimattam (Journal of Dharma, 1994)
The content of this issue of the Journal of Dharma is mainly papers presented at the international seminar organized by the Centre for the Study of the World Religions ot Dharmaram Vidya Kshetram Bangalore, August 17 and 18, 1993, to mark the centenary of the World Parliament of Religions (Chicago, 1893). The theme of the seminar was "The Future of Interreligious Dialogue: Threats and Promises." The topic is particularly relevant today in India, which is undergoing a serious crisis owing to the use and abuse of religion by political parties. Today there is an upsurge of religious famentalism. Each religion is claiming a sort of superiority over 'others, and proclaiming Its Scriptures, tradition and religious culture itself as the one absolute norm to be imposed on all. Since religious · faith is a divine gift shared by all believers, what sets up one religion against another is mostly the absolutization of the trivial, which is the heart of the fundamentalist attitude.